Trend of Nutritional Support in Preterm Infants - Man-Yau Ho; Yu-Hsuan Yen (Pediatrics and Neonatology)
Without appropriate nutritional support, preterm infants fail to grow after birth and have malnutrition. The main reason for delayed feeding is fear of immaturity of gastrointestinal function. The principles of nutritional practice should be as follows: (1) minimal early initiation of enteral feeding with breast milk (0.5–1 mL/h) to start on Day 1 if possible and gradual increase as tolerated; (2) early aggressive parenteral nutrition as soon as possible; (3) provision of lipids at rates that will meet the additional energy needs of about 2–3 g/kg/d; and (4) attempt to increase enteral feeding rather than parenteral nutrition.